Complaints in Travel Reality Shows: A Comparison Between Korean and Chinese Speakers - Weihua Zhu (Languages)
This study compares complaints in Korean and Chinese, focusing on how they are expressed explicitly or implicitly. Complaints are potentially face-threatening, yet they frequently appear in conversations among native Korean and Chinese speakers who are characterized as upholding Neo-Confucian values and emphasizing social harmony. Although some contrastive studies have examined complaints across languages, none have specifically investigated the explicit and implicit strategies employed in Korean and Chinese complaint discourse. Given the growing intercultural contact between Korean and Chinese speakers, this gap calls for closer attention. To address this, the present study explores how native Korean and Chinese speakers articulate complaints in the Korean and Chinese versions of the travel reality show Sisters Over Flowers. Sixteen episodes were analyzed using interactional sociolinguistic methods, incorporating both qualitative and quantitative approaches. The analysis uncovered both explicit and implicit strategies (e.g., expressions of annoyance or disapproval, overt grievances, questions, advice, teasing, and hints). Notably, the Korean participants produced significantly fewer complaints than their Chinese counterparts. These findings offer theoretical and practical insights. Theoretically, the results challenge overly broad notions of East–West pragmatic distinctions by demonstrating meaningful variation within East Asian cultures. Practically, a better understanding of explicit and implicit complaint strategies in Korean and Chinese can enhance intercultural communication, promote culturally sensitive responses, and bridge misunderstandings in increasingly globalized settings.